A Review on Novel Ligand Targeted Delivery for Cardiovascular Disorder - Jaiswal, Shweta; Rajnikanth, P.S.; Thakur, Sunita; Deepak, Payal; Anand, Sneha (Current Drug Delivery, 2021)
Cardiovascular diseases cover various disorders like ischemic heart disease, hyperlipidemia, atherosclerosis, myocardial infarction, hypertension, etc. There are many synthetic drugs available for the treatment of cardiovascular therapy. However, they have several drawbacks like high dosing, toxicity, elevated blood potassium levels, low blood pressure, gastrointestinal issues, etc. To overcome these side effects of synthetic drugs, targeting the drug to the specific cardiac tissue is the best novel method in cardiovascular therapy. The highest targeting efficacy of ligand- based therapy with proper mechanisms and improved expandability provides a novel therapeutic strategy in cardiovascular diseases. Ligand therapy is more cost-effective compared to cell- based therapy. The surface area of protein is much larger than the orally bioavailable drug. Therefore, the targeting of various less active drug molecules to the particular ligand can be possible. The efficacy of ligands to induce cardiomyocytes proliferation has been ratified. The fact that ligand- based approaches are effective for cardiac transformation has been pointed out. Ligands interact with proteins in target cells, which are influenced by chemical signals. These various receptors selectively bind to biased ligands and energize the intracellular signaling pathway. The ligands can directly stabilize the active receptor conformations by a non-standard connective site. The key function of ligands is functional selectivity, which enhances the therapeutic efficacy and minimizes the side effects of drugs through the interpretation of signal transduction pathways. This review covers the role and effectiveness of novel ligands in cardiovascular disorders.
Keywords: adropin